2017
DOI: 10.1084/jem.20170193
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of latently infected CD4+ T cells carrying replication-competent HIV-1: Potential role in latent reservoir dynamics

Abstract: The latent reservoir for HIV-1 in resting CD4+ T cells prevents cure with antiretroviral therapy. Hosmane et al. provide evidence supporting the hypothesis that a larger fraction of cells in the reservoir is generated by cell proliferation than by direct infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
383
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 335 publications
(425 citation statements)
references
References 74 publications
26
383
2
Order By: Relevance
“…The detection of identical intact proviruses suggests a role for cellular proliferation in the maintenance and stability of the latent replication-competent reservoir. Unlike Hosmane et al (2017), Bui et al (2017) and Lorenzi et al (2016), who used the definitive viral outgrowth assay to identify identical replication-competent proviruses in participants on ART, we did not employ in vitro studies to confirm the replication-competency of intact proviruses identified by FLIPS. Therefore, we cannot be certain that the identical intact proviruses we identified are truly replication-competent.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of identical intact proviruses suggests a role for cellular proliferation in the maintenance and stability of the latent replication-competent reservoir. Unlike Hosmane et al (2017), Bui et al (2017) and Lorenzi et al (2016), who used the definitive viral outgrowth assay to identify identical replication-competent proviruses in participants on ART, we did not employ in vitro studies to confirm the replication-competency of intact proviruses identified by FLIPS. Therefore, we cannot be certain that the identical intact proviruses we identified are truly replication-competent.…”
Section: Discussionmentioning
confidence: 99%
“…However, viral reactivation in response to TCR-induced signals follows a stochastic pattern (16,27), implying that clonal expansion can at least sometimes occur in the absence of viral reactivation. Whether the efficacy of viral reactivation in functionally polarized cells is influenced by signature transcription factors of polarized T cells is currently unknown; however, it is noteworthy that GATA-3 and c-Maf, two transcription factors involved in regulating Th2-polarization, can stimulate HIV-1 expression through direct interactions with the HIV-1 promoter (28,29); this may facilitate immune-mediated clearance of HIV-1-infected Th2 cells and correspond to the very low frequency of clonally-expanded Th2 cells encoding intact HIV-1 in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This functional profile might be conducive to stabilizing the pool of latently HIV-1-infected cells, as it may allow for amplifying the viral reservoir through clonal expansion of HIV-1-infected cells. Indeed, clonal expansion of HIV-1-infected cells has previously been noted in several studies (12,13), and there is increasing evidence that clonal proliferation may also occur in cells encoding for replication-competent HIV-1 (14)(15)(16)(17). Here, we used massive near-full-length single-genome viral sequencing to profile HIV-1 reservoirs in CD4 + T cells with distinct functional polarizations.…”
Section: Introductionmentioning
confidence: 97%
“…The persistence of long-lived infected cells has been shown by many studies (37-40) and was illustrated further by the finding that HIV-1-infected cells can clonally expand both prior to and during ART (1, 2, 31), resulting in populations of cells with identical proviruses and identical integration sites in the blood and tissues (1). More recently, expanded clones harboring replication-competent proviruses were identified by sequence matches between viruses recovered in multiple different viral outgrowth cultures, revealing that most of the HIV reservoir is maintained by cellular proliferation (4,5,41). Furthermore, proviruses with identical sequences, and thus likely to be in cell clones, were reported to be a source for rebound viremia after stopping ART (12).…”
Section: Discussionmentioning
confidence: 99%